Companies in Indonesia Towards the Implementation of Integrated Reporting - Devica Pratiwi; Ilham Ilham; Della Verati; Santia Veronika; Sharon Gabriella (DINASTI RESEARCH, 2023)
Reports that not only disclose financial information, but also non-financial information that describes the company's overall activities present integrated information are known as integrated reporting. This research was conducted to find out whether companies in Indonesia are ready to switch to integrated reporting. The objects are the annual report and sustainability report of 16 companies from LQ45 listed on the IDX from 2017 to 2019. Data analysis techniques use content analysis based on the International <IR> Framework guidelines which focus on content elements. The results of the disclosure of the annual report and the sustainability report of 16 companies show that in general the companies have presented and disclosed the seven elements contained in the guidelines, namely the organizational overview and external environment, governance, business models, risks and opportunities, strategy and resource allocation, performance and outlook with an average value in the range of 3,563 – 4,958 from a maximum value of 5,00.